ANTIBACTERIAL EFFECTIVENESS OF 2% CHITOSAN AND 2% CHLORHEXIDINE AGAINST ENTEROCOCCUS FAECALIS IN BIOFILM (LABORATORY EXPERIMENT) - SIMANJUNTAK, PRISCILLA ARLYTA; DJAUHARIE, NILAKESUMA; NURSASONGKO, BAMBANG (International Journal of Applied Pharmaceutics, 2019)
Objective: Enterococcus faecalis can form biofilms and has a major role in the etiology of persistent lesions after root canal. We analyzed the efficacy of chitosan and chlorhexidine against E. faecalis in biofilms. Methods: Polymerase chain reaction was used to analyze E. faecalis DNA that survived and lived after immersing the biofilm in an antibacterial solution. Results: A statistically significant difference was noted in living E. faecalis between chitosan and control and between 2% chlorhexidine and control groups (p≤0.05). No significant difference was noted between chitosan and chlorhexidine groups (p>0.05). Conclusions: Antibacterial effectivity of chitosan is equal to that of chlorhexidine against E. faecalis in biofilm.